30th Annual International Computer Software and Applications Conference (COMPSAC'06) 2006
DOI: 10.1109/compsac.2006.80
|View full text |Cite
|
Sign up to set email alerts
|

Test Case Prioritization Using Relevant Slices

Abstract: Software testing and retesting occurs continuously during the software development lifecycle to detect errors as early as possible. The sizes of test suites grow as software evolves. Due to resource constraints, it is important to prioritize the execution of test cases so as to increase chances of early detection of faults. Prior techniques for test case prioritization are based on the total number of coverage requirements exercised by the test cases. In this paper, we present a new approach to prioritize test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 17 publications
(56 reference statements)
0
52
0
1
Order By: Relevance
“…MC/DC is a very powerful technique for verification and it is found that if test cases meet MC/DC coverage need then they can detect important errors that can't be found by functional testing. Jeffrey et al presented a method of prioritization based on the relevant slices of outputs of various test cases [16]. This technique is a combination of total statement coverage criterion and also depends upon the number of statements covered by a test case that influence the output generated by that test case.…”
Section: Related Workmentioning
confidence: 99%
“…MC/DC is a very powerful technique for verification and it is found that if test cases meet MC/DC coverage need then they can detect important errors that can't be found by functional testing. Jeffrey et al presented a method of prioritization based on the relevant slices of outputs of various test cases [16]. This technique is a combination of total statement coverage criterion and also depends upon the number of statements covered by a test case that influence the output generated by that test case.…”
Section: Related Workmentioning
confidence: 99%
“…Among all these algorithms, GRASP surpassed the simulated annealing, genetic and greedy algorithm. Dennis et al [22] invented prioritization technique using relevant slice. A program includes a lot of statements.…”
Section: Cost=ps * ∑ N I=2 (Cs (I) +Co I (I) +Co (I)+b(i) * Cv I (I)+mentioning
confidence: 99%
“…Jeffrey and Gupta [15] present an algorithm that prioritizes test cases which combined statements coverage and relevant slices of the outputs of test cases. Khalilian et al [16] prioritize test cases according to the available historical performance data which obtained from the previous test sessions.…”
Section: Related Workmentioning
confidence: 99%